Pengembangan Aplikasi Multimedia Pembelajaran Interaktif untuk Mata Pelajaran Bahasa Indonesia - Syamsiah Syamsiah (SAP (Susunan Artikel Pendidikan), 2017)
The increasingly rapid development of technology, especially computer, creates an impact on the use of computer in education. Computers can be used as one of interactive learning media. To facilitate the delivery of learning materials to students, there must be an interesting packaging of materials in the form of multimedia that is educative and entertaining for them. The objective of this research is to make an application of interactive multimedia-based Indonesian language learning as an alternative learning medium that is easy to learn and understand by students with an edutainment concept at Bimbel D-LLA COURSE. The application is made by using software Macromedia Flash. It is made using observation and literature review methods. From the result of the research, it can be concluded that the application of interactive Indonesian language learning has been successfully made with six menus, namely: 4 types of exercises (knowing letters on keyboard, learning syllabification, guessing images and arranging letters) and 2 types of games (catching words on eggs, matching pictures and words). Besides, the fitness of this application has also been tested using SQL.